Effect of Centrifugation of Stallion Semen Through a Low Density Colloid Prior to Freezing on Sperm Cryosurvival - Ziyad Al-Kass; Jane M. Morrell; Theodoros Ntallaris (Animals, 2025)
Sperm quality is adversely affected by cryopreservation due to the increased production of reactive oxygen species, which affects the integrity of sperm membranes, motility, and DNA fragmentation. Three methods for removing seminal plasma, washing (centrifuging extended semen at 800× g for 10 min) and Single Layer Centrifugation with high or low density Equicoll, were used to prepare 29 ejaculates from ten stallions for freezing. Sperm quality parameters (kinematics, plasma membrane integrity, superoxide and hydrogen peroxide production, mitochondrial membrane potential, and DNA fragmentation) were evaluated before and after freezing using kinematic and flow cytometric analysis. The parameters for fresh samples were within the normal range for stallion semen but were lower after thawing. There were few differences between the three preparation methods. Interestingly, DNA fragmentation was affected most by the sperm preparation method, being lowest for SLC through high density Equicoll, although SLC through low density Equicoll was effective for some stallions. Some differences were observed in the proportions of live or dead spermatozoa positive for hydrogen peroxide. In conclusion, all of these methods would be suitable for the preparation of semen prior to cryopreservation, but Single Layer Centrifugation through high density Equicoll was the most effective in removing spermatozoa with damaged DNA.